Islam, Local Wisdom and Religious Harmony: Religious Moderation in East-Java Christian Village Bases - Umi Sumbulah; Agus Purnomo; Jamilah Jamilah (UIN Maulana Malik Ibrahim Malang, 2022)
This article discusses about the dynamics of interaction and harmony among believers in 41 Christian villages spread over 15 districts in East Java. Although called the Christian Villages, they are populated by Muslims, Catholics, Hindus, and Buddhists. The social diversity is formed through kinship and marriage. The Christian villages, which are called “Pancasila Villages” and “Villages of Diversity”, are melting pots that unite all wisdom, teachings, mythology, and religious traditions. The current qualitative research conducted in Christian villages in Jombang, Malang, and Situbondo go into the following results: first, the esoteric-inclusive interpretation that religion is a way of life that directs its adherents to achieve peace and happiness becomes the basis for religious people to respect each other and guarantee religious freedom; second, interfaith awareness that all religions have an exoteric dimension in the variety of rites to approach God is a basic principle in building harmony; third, the diversity meaning of symbols in the form of values, rituals, and sacred objects are embodied in the interactions of daily life. Religious moderation manifests in tolerance, inclusivism, equality, and cooperation in various cultural spaces. Further researches on interaction pattern and level of religious moderation would be worth investigating. Artikel ini membahas dinamika interaksi dan kerukunan umat beragama di basis desa Kristen yang berjumlah 41 desa yang tersebar di 15 kabupaten di Jawa Timur. Meski disebut Desa Kristen, desa ini juga dihuni pemeluk Islam, Katolik, Hindu, dan Budha. Keberagaman masyarakat terbentuk melalui kekerabatan dan perkawinan. Basis Desa Kristen yang dijuluki “Desa Pancasila” dan “Desa Keragaman” adalah melting pot yang menyatukan semua kearifan, ajaran, mitologi, dan tradisi keagamaan. Hasil penelitian kualitatif yang dilakukan di desa-desa Kristen di Jombang, Malang, dan Situbondo ini menunjukkan: pertama, interpretasi esoteris-inklusif bahwa agama adalah cara hidup yang mengarahkan pemeluknya untuk mencapai kedamaian dan kebahagiaan, menjadi dasar bagi umat beragama untuk saling menghormati dan menjamin kebebasan beragama. Kedua, kesadaran lintas agama bahwa semua agama memiliki dimensi eksoteris dalam ragam ritus untuk mendekati Tuhan merupakan prinsip dasar dalam membangun harmoni. Ketiga, makna keragaman simbol berupa nilai, ritual, dan benda sakral diwujudkan dalam interaksi kehidupan sehari-hari. Moderasi beragama terwujud dalam toleransi, inklusivisme, kesetaraan, dan kerjasama dalam berbagai ruang budaya. Penelitian lebih lanjut tentang pola interaksi dan tingkat moderasi beragama layak dilakukan.